Legal Protection and Accountability of Nurses Performing Delegated Medical Actions in Remote Government Health Services - Atmaja, Deni; Sapsudin, Asep (Research Horizon, 2026)
In remote Indonesian islands with scarce doctors, nurses often perform physician-level medical procedures to maintain urgent patient care. These necessary actions expose them to legal risks if viewed as exceeding their authority. This study examines legal protection and accountability for nurses undertaking such tasks under government duties at a regional general hospital in a remote island setting. The research maps existing legal safeguards for nurses and the forms of responsibility they hold under Indonesian law. A qualitative study combined normative legal analysis with empirical field data from all thirty-six nurses, using questionnaires, interviews, observations, and document review. Descriptive analysis contrasted legal standards with actual practice. Nurses show reasonable awareness of basic legal foundations and hospital tools like standard operating procedures and delegated authority. However, delegation is frequently undocumented, competency checks are irregular, and understanding of dispute safeguards is limited. Accountability is well-defined across administrative, civil, and criminal levels, yet practical administrative support remains inconsistent. Stronger regional policies, regular legal training, mandatory written delegations, and accessible legal assistance are urgently needed to reduce vulnerability, build confidence, and ensure safer, more equitable healthcare in isolated areas.